RELASI SEMANTIK BAHASA MELAYU DIALEK KETAPANG - Sumiati, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrackÂ This study deals with the linguistic field. Researchers focus on semantic research issues that are relationships between forms and meanings that involve synonyms and polysemics, relations between two meanings involving hyponim and antonyms, and relations between two forms involving homonyms. The method used in this research is descriptive method with qualitative research form. Sources of data in this study are native speakers Ketapang dialect Malay language obtained through observation and recording field directly. The data in the study are related to synonyms, antonyms, polysemics, hyponimes, and homonyms. The technique used in this research is direct technique that is simak method, skill method and documentary study. The data collection tools used in this research are questionnaires, picture lists, and folklore. Based on the results of existing data analysis, it can be concluded that in Ketapang dialect Malay language there are 157 words containing semantic relation, 52 synonyms consist of 13 complete and total synonyms, 21 complete but not total synonyms, 10 synonyms incomplete but total, 8 synonyms Complete and not total. 65 antonyms consisting of 30 twin antonyms, 13 polar antonyms, 11 relational antonyms, 5 hierarchial antonyms, and 6 compound antonyms. 13 polysemics, 13 hyponimes, and 14 hyponimes.Â Keywords: Synonyms, Polysemic, Hyponim, Antonim, and Homonym.